Expert Consensus on Optimal Acquisition and Development of the International Bowel Ultrasound Segmental Activity Score [IBUS-SAS]: A Reliability and Inter-rater Variability Study on Intestinal Ultrasonography in Crohn's Disease. (24th October 2020) - Novak, Kerri L; Nylund, Kim; Maaser, Christian; Petersen, Frauke; Kucharzik, Torsten; Lu, Cathy; Allocca, Mariangela; Maconi, Giovanni; de Voogd, Floris; Christensen, Britt; Vaughan, Rose; Palmela, Carolina; et al.
Abstract: Background and Aims: Intestinal ultrasound [IUS] is an accurate, patient-centreed monitoring tool that objectively evaluates Crohn's disease [CD] activity. However no current, widely accepted, reproducible activity index exists to facilitate consistent IUS identification of inflammatory activity. The aim of this study is to identify key parameters of CD inflammation on IUS, evaluate their reliability, and develop an IUS index reflecting segmental activity. Methods: There were three phases: [1] expert consensus Delphi method to derive measures of IUS activity; [2] an initial, multi-expert case acquisition and expert interpretation of 20 blinded cases, to measure inter-rater reliability for individual measures; [3] refinement of case acquisition and interpretation by 12 international experts, with 30 blinded case reads with reliability assessment and development of a segmental activity score. Results: Delphi consensus: 11 experts representing seven countries identified four key parameters including: [1] bowel wall thickness [BWT]; [2] bowel wall stratification; [3] hyperaemia of the wall [colour Doppler imaging]; and [4] inflammatory mesenteric fat. Blind read: each variable exhibited moderate to substantial reliability. Optimal, standardised image and cineloop acquisition were established. Second blind read and score development: intra-class correlation coefficient [ICC] for BWT was almost perfect at 0.96 [0.94–0.98]. All four parameters correlated with the global disease activity assessment and were included in the final International Bowel Ultrasound Segmental Activity Score with almost perfect ICC (0.97 [0.95–0.99, p <0.001]). Conclusions: Using expert consensus and standardised approaches, identification of key activity measurements on IUS has been achieved and a segmental activity score has been proposed, demonstrating excellent reliability.